2019
DOI: 10.3390/met9101093
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Shot Peening and Deep Rolling on the Fatigue Response of High Strength Fasteners

Abstract: Shot-peening and deep rolling are mechanical surface treatments that are commonly applied to enhance the fatigue performances of components, owing to their capacity to generate compressive residual stresses and induce work hardening. However, literature is still poor of published data concerning the application of these treatments to high strength steels fasteners, although these represent a class of components among the most widespread. In the present work, the impact of deep rolling and shot-peening performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Alternating bending preliminary tests showed little or no crack growth before component failure occurred. It has been shown that the SP compressive effect surpasses rugosity´s negative effects incrementing fatigue life [28], [29]. Therefore, choosing the option that maximizes the S-N span of the component makes sense.…”
Section: Discussionmentioning
confidence: 99%
“…Alternating bending preliminary tests showed little or no crack growth before component failure occurred. It has been shown that the SP compressive effect surpasses rugosity´s negative effects incrementing fatigue life [28], [29]. Therefore, choosing the option that maximizes the S-N span of the component makes sense.…”
Section: Discussionmentioning
confidence: 99%
“…The material mechanical properties were initially assessed by static tensile tests, which led to the estimation of a tensile strength ranging between 1300 MPa and 1350 MPa and of an average 1100 MPa yield point, with 9% as minimum percentage elongation at fracture. In addition, screws with the same specifications were involved in a fatigue testing campaign, as described in [17].…”
Section: Methodsmentioning
confidence: 99%
“…Their comparison led to the selection of the 35% incremented load that was able to maximize the fatigue strength. Further details are available in [17]. Two photos depicting a typical device for deep-rolling with 120 • spaced rollers (screw to be applied at the centre) and a stage of the treatment are shown in Figure 2a,b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the studies pertaining to DR were on standard test specimens or similar components because of the obvious limitations of tooling and experimentation for application prototypes. Nevertheless, there are satisfactory efforts available on DR of components such as turbine/compressor blades [104][105][106], aircraft structural components [8,21], axels [107][108][109], shafts [110,111], crankshafts [112][113][114], tension bolts [115], high-strength fasteners and threaded parts [116,117], connecting rod screws [118], torsion bars [119,120], gear tooth [83], roller and thrust bearing race/rings [78,96,121], welded joints [122][123][124][125][126], blanking punch fillets [22], hip implants [26,27], etc. When deep-rolled, all these applications exhibited significant improvement in fatigue performance, which was attributed to substantial strain hardening, higher magnitude and deeper penetration of CRS, tailored surface region microstructure, and increased boundary layer hardness along with an improved surface finish.…”
Section: The Deep Rolling Processmentioning
confidence: 99%